Mempertahankan Kualitas Produksi Kopi dengan Metode Kalibrasi pada Coffe Shop Kaldi.id - Djoko Hananto; Jehan Zachry Ibrahim; David Ferdiansyah; Muhamad Kemal Muyassar; Syabil Akbar Az-Zuhri; Krisna Amartha Elang; Shinta Destian; Dannoval Ramadhan; Sayyida Nabeela Nurmezhiya Qosyasyh (Jurnal Multidisiplin Indonesia, 2024)
Abstract: This research aims to explore the application of the calibration method in the coffee production process at Kaldi.id and its impact on product quality. The research method used is a case study with a qualitative approach, involving in-depth interviews, participant observation and document analysis. The research results show that Kaldi.id has succeeded in maintaining consistent coffee quality through the use of strict calibration methods, both for hot and cold coffee. Apart from that, friendly customer service and comfortable facilities such as the policy of using your own tumbler and billiard table are also supporting factors for customer satisfaction. In conclusion, this comprehensive approach has helped Kaldi.id differentiate itself in the coffee industry by creating a satisfying experience for customers.